Competitive binding of Cd and Zn with the phytochelatin (gamma-Glu-Cys)4-Gly: comparative study by mass spectrometry, voltammetry-multivariate curve resolution, and isothermal titration calorimetry. - Chekmeneva,E; Prohens,R; Díaz-Cruz,JM; Ariño,C; Esteban,M (Environ Sci Technol, 2008)
The competitive binding of Cd2+ and Zn2+ by the phytochelatin (gamma-Glu-Cys)4-Gly (PC4) has been examined using several techniques. Electrospray ionization mass spectrometry is used to determine the stoichiometries of the complexes, while voltammetric data analyzed by multivariate curve resolution with alternating least squares allows one to not only trace the displacement induced by Cd2+ or Zn2+ in the binding of Zn2+ or Cd2+, respectively, by PC4, but also to obtain a complete overview of the processes involved. Isothermal titration calorimetry is used to determine the related binding and thermodynamic parameters. Results obtained via these different techniques are compared and discussed below. The formation of ternary CdZn(PC4) and Cd2Zn(PC4) complexes was observed.